PERAN INDONESIA DALAM MENJAGA KEAMANAN TRANSPORTASI DAN NAVIGASI LAUT MELALUI KEANGGOTAAN DEWAN INTERNATIONAL MARITIME ORGANIZATION (IMO) - Algola Trisakti; Irwan Iskandar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Indonesia is an archipelagic country where its geographical position and conditions not only place Indonesia as a country that has a strategic position for international shipping, but also pose considerable challenges. A portrait of maritime security issues in Indonesia includes identifying trends in maritime security. To secure such a vast sea, no single country is able to do it alone. Indonesia's success in selecting members of the IMO Council certainly poses a challenge to Indonesia to improve the security and safety of efficient shipping while also increasing the protection of the marine environment. This research is theoretically built using role theory in foreign policy and supported by the concept of national interests. The formulation of all arguments, data, facts, and theoretical frameworks in this study uses a qualitative descriptive method. This study also uses the nation-state as a level of analysis. The result of this study is that Indonesia's re-election as a member of the IMO Category-C board provides a role in realizing the security of Indonesia's maritime transportation and navigation through the Traffic Separation Scheme (TSS) policy in the Sunda Strait and Lombok Strait, where the use of TSS is a separation scheme system shipping lanes of ships going in opposite directions in a busy and narrow shipping lane in order to avoid ship accidents that often occur in the two straits due to the density of ship traffic lanes. Keywords: IMO, Traffic Separation Scheme (TSS), World Maritime Fulcrum, foreign policy